2016
DOI: 10.1002/2015ja022251
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of midlatitude electron density enhancement using total electron content measurements

Abstract: Using the global ionospheric map of total electron content in 2002–2009, this paper investigates anomalous, midlatitude electron density enhancement (MEDE) bounded by a tropical electron density trough and the usual midlatitude electron density trough at all times (24 h) of the day for the first time. The diurnal, seasonal, and longitudinal variations in the occurrence and strength of MEDE are studied at solar maximum (2002) and long deep solar minimum (2009), and latitude‐longitude dependence is examined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…[], and Rajesh et al . [] concluded that latitudinal pattern of the nighttime N m F 2 enhancement is the result of impact of both mechanisms together with possible influence of cross‐ L plasma motion due to zonal electric fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[], and Rajesh et al . [] concluded that latitudinal pattern of the nighttime N m F 2 enhancement is the result of impact of both mechanisms together with possible influence of cross‐ L plasma motion due to zonal electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…Although the plasmasphere is the primary nighttime source of ions, equatorward neutral winds are also considered as contributor to increases of N m F 2 at night by keeping ions at greater heights where the loss rates are smaller [Rishbeth, 1972;Anderson and Klobuchar, 1983;Bailey et al, 1991;Jee et al, 2005]. Balan and Rao [1987], Balan et al [1991], and Rajesh et al [2016] concluded that latitudinal pattern of the nighttime N m F 2 enhancement is the result of impact of both mechanisms together with possible influence of cross-L plasma motion due to zonal electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…At ionosphere mid-latitudes, the nighttime electron density enhancement has been observed and reported by previous studies (e.g., Bailey et al 1991;Farelo et al 2002;Dabas and Kersley 2003;Luan et al 2008;Park et al 2008;Chen et al 2011Chen et al , 2012Chen et al , 2013Lin et al 2011;Rajesh et al 2016). This density-enhanced ionospheric feature appeared more frequently during solar minimum conditions (Bailey et al 1991), and it is suggested to be caused by larger downward plasma flux from the plasmasphere during the nighttime (Mikhailov et al 2000;Farelo et al 2002;Dabas and Kersley 2003).…”
Section: Introductionmentioning
confidence: 52%
“…Usually, TEC is calculated using phase and code delays of GNSS satellites signals received by dual-frequency ground receivers. The ionosphere is represented by a thin shell of zero thickness at the altitudes of the ionospheric F region when calculating TEC (Schaer et al, 1995;Komjathy, 1997). Though TEC is an integral characteristic (electron content from the satellite to the ground), it is assumed that it characterizes the state of the F region of the ionosphere.…”
Section: Introductionmentioning
confidence: 99%